Aerosol physicochemical determinants of carbon black and ozone inhalation co-exposure induced pulmonary toxicity. (27th October 2022) - Majumder, Nairrita; Kodali, Vamsi; Velayutham, Murugesan; Goldsmith, Travis; Amedro, Jessica; Khramtsov, Valery V; Erdely, Aaron; Nurkiewicz, Timothy R; Harkema, Jack R; Kelley, Eric E; Hussain, Salik
Abstract: Air pollution accounts for more than 7 million premature deaths worldwide. Using ultrafine carbon black (CB) and ozone (O3 ) as a model for an environmental co-exposure scenario, the dose response relationships in acute pulmonary injury and inflammation were determined by generating, characterizing, and comparing stable concentrations of CB aerosols (2.5, 5.0, 10.0 mg/m 3 ), O3 (0.5, 1.0, 2.0 ppm) with mixture CB + O3 (2.5 + 0.5, 5.0 + 1.0, 10.0 + 2.0). C57BL6 male mice were exposed for 3 h by whole body inhalation and acute toxicity determined after 24 h. CB itself did not cause any alteration, however, a dose response in pulmonary injury/inflammation was observed with O3 and CB + O3 . This increase in response with mixtures was not dependent on the uptake but was due to enhanced reactivity of the particles. Benchmark dose modeling showed several-fold increase in potency with CB + O3 compared with CB or O3 alone. Principal component analysis provided insight into response relationships between various doses and treatments. There was a significant correlation in lung responses with charge-based size distribution, total/alveolar deposition, oxidant generation, and antioxidant depletion potential. Lung tissue gene/protein response demonstrated distinct patterns that are better predicted by either particle dose/aerosol responses (interleukin-1β, keratinocyte chemoattractant, transforming growth factor beta) or particle reactivity (thymic stromal lymphopoietin, interleukin-13, interleukin-6). Hierarchical clustering showed a distinct signature with high dose and a similarity in mRNA expression pattern of low and medium doses of CB + O3 . In conclusion, we demonstrate that the biological outcomes from CB + O3 co-exposure are significantly greater than individual exposures over a range of aerosol concentrations and aerosol characteristics can predict biological outcome.